2011
DOI: 10.1098/rsta.2011.0240
|View full text |Cite
|
Sign up to set email alerts
|

Image-based multi-scale modelling and validation of radio-frequency ablation in liver tumours

Abstract: The treatment of cancerous tumours in the liver remains clinically challenging, despite the wide range of treatment possibilities, including radio-frequency ablation (RFA), highintensity focused ultrasound and resection, which are currently available. Each has its own advantages and disadvantages. For non-or minimally invasive modalities, such as RFA, considered here, it is difficult to monitor the treatment in vivo. This is particularly problematic in the liver, where large blood vessels act as heat sinks, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 41 publications
0
48
0
3
Order By: Relevance
“…Small ones are represented implicitly in the parenchyma as a porous medium using the Wulff and Klinger model [8]. The bioheat equation is weakly coupled to a computational fluid dynamics (CFD) solver to accurately take into account the effect of blood circulation on the dissipated heat, while the blood flow in the porous tissue is computed by solving the Darcy's equation [9]. The heat transfer depends on the blood flow, which is not modified as the organ is heated (the effect of heat on the viscosity of the flow is neglected as well as the coagulation effect).…”
Section: Introductionmentioning
confidence: 99%
“…Small ones are represented implicitly in the parenchyma as a porous medium using the Wulff and Klinger model [8]. The bioheat equation is weakly coupled to a computational fluid dynamics (CFD) solver to accurately take into account the effect of blood circulation on the dissipated heat, while the blood flow in the porous tissue is computed by solving the Darcy's equation [9]. The heat transfer depends on the blood flow, which is not modified as the organ is heated (the effect of heat on the viscosity of the flow is neglected as well as the coagulation effect).…”
Section: Introductionmentioning
confidence: 99%
“…This was a simplified FEM model since in-vivo the liver is a very complex electrical and thermal organ due to its inhomogeneity and three different types of blood vessels of different diameters and flow velocities. FEM models used to study the influence of blood vessel can be found from literature such as [19]. We also realize that FEM modelling has its accuracy limitation in mesh size selection.…”
Section: F Experimental Evaluationmentioning
confidence: 99%
“…FEM modelling was used to analyses radiofrequency cancer ablation [17] by solving RF Joule (resistive) heating and Penne's bio-heat equation [18]. FEM modelling was further used to study the influence of blood vessel on the thermal lesion formation (the heat sink effects) during RFA [19] and the influence of other parameters such as water evaporation [20] and tissue conductivities with efficient RFA experiment design [21,22]. In this study, an anatomical 3D FEM model was used for RFA simulation.…”
Section: B 3d Fem Modellingmentioning
confidence: 99%
“…The problem is further confounded by the difficulty of monitoring the ablation process itself [4,5]. Patient-specific image-based 3D modeling could resolve these problems by permitting pre-treatment planning of the simulated thermal ablation based on preoperative images of the lesion [6].…”
Section: Introductionmentioning
confidence: 99%